2022
DOI: 10.1016/j.clnu.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 in nutritional and functional status of survivors admitted in intensive care units during the first outbreak. Preliminary results of the NUTRICOVID study

Abstract: Background & aims: COVID-19 patients present a high hospitalization rate with a high mortality risk for those requiring intensive care. When these patients have other comorbid conditions and older age, the risk for severe disease and poor outcomes after ICU admission are increased. The present work aims to describe the preliminary results of the ongoing NUTRICOVID study about the nutritional and functional status and the quality of life of adult COVID-19 survivors after ICU discharge, emphasizing the in-hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
4
32
0
1
Order By: Relevance
“…Among the 2 studies conducted in Spain (41,44), the pooled prevalence of sarcopenia was 89.1% (95% CI: 86.3 to 91.7%, k = 2, I 2 = 15.4%, p = 0.277). The prevalence in the 4 Italy studies (25, 30, 50, 51) was 49.2% (95% CI: 33.6 to 65.0%, k = 4, I 2 = 91.17%, p = 0.000).…”
Section: Study Locationmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the 2 studies conducted in Spain (41,44), the pooled prevalence of sarcopenia was 89.1% (95% CI: 86.3 to 91.7%, k = 2, I 2 = 15.4%, p = 0.277). The prevalence in the 4 Italy studies (25, 30, 50, 51) was 49.2% (95% CI: 33.6 to 65.0%, k = 4, I 2 = 91.17%, p = 0.000).…”
Section: Study Locationmentioning
confidence: 98%
“…For sarcopenia assessment methods, five studies (26,30,33,42,47) (32,50) and BIA (48,51), which were used by two studies each and yielded a pooled prevalence of 26.7 (95% CI: 23.2 to 30.5%, k = 2, I 2 = 98.90%, p = 0.000) and 0.4% (95% CI: 0.1 to 0.8%, k = 2, I 2 = 97.70%, p = 0.000), respectively. For parameters used to measure sarcopenia, seven studies used skeletal muscle index (SMI) with a pooled prevalence of 49.0% (95% CI: 31.3 to 66.9%, k = 7, I 2 = 97.03%, p = 0.000) (25,29,33,42,47,52,53), 4 studies used SARF-score with a prevalence of 73% (95% CI: 49.3 to 91.3%, k = 4, I 2 = 98.00%, p = 0.000) (31,41,44,45), and two studies used HGS with a prevalence of 26.7% (95% CI: 23.2 to 30.5%, k = 2, I 2 = 98.90%, p = 0.000) (32,50). The subgroup meta-analysis result of parameters used in the remaining studies is shown in Table 3 and Supplementary Figure 6.…”
Section: Diagnostic Criteria Of Sarcopeniamentioning
confidence: 99%
“…En el mes de noviembre lo haremos en el congreso de la propia SENDIMAD, que le dedicará un espacio en una mesa redonda. Además, ya está aceptado un artículo en Clinical Nutrition con datos preliminares (6).…”
Section: Dra Julia áLvarezunclassified
“…Finally, recent preliminary data have shown a high percentage of malnutrition also among patients who survived at COVID-19 [7] , highlighting the clinical relevance of poor nutritional status not only at baseline, conditioning patients outcomes during ICU stay, but also developed during hospital stay, suggesting the urgent need for clear nutritional therapeutic interventions in this setting.…”
mentioning
confidence: 96%